Training Needs Assessment of College Faculty: Its Impact on Professional Development and Teaching Motivation - Tomas, Maria Anita; Tiquia, Lea Carmela (JPAIR Institutional Research, 2022)
The research aimed to evaluate the training needs of the SMCB college teaching personnel for the quality improvement of seminars and trainings that will be organized and conducted responding to the identified current needs of the teachers. As an aftermath of this assessment survey, the Training Needs Assessment “Action Plan” was formulated to respond to the current needs of the college faculty. Survey results show the areas for improvement in terms of the current level of professional expertise on (1) problem solving and the use of varied technology applications and tools in teaching amid digital disruption; (2) personal needs in terms of developing and maintaining mental and emotional wellness amidst pandemic; and, (3) one’s social skills and financial stability. This study employed a qualitative descriptive research design and had teacher respondents from all the programs. The statistical tools utilized in this study were frequency counts, ranking, and weighted mean. The study shows that the perceived need of the faculty depends on the number of years in service, age, and educational background. The significant difference between the mean of the group was when the variables were used for continuing education.
Keywords: training needs assessment; professional development program; digital disruption; information; communication; and technology; descriptive; Philippines